2017
DOI: 10.3892/mco.2017.1211
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lifestyle, hormonal and medical factors in women with sporadic and Lynch syndrome-associated endometrial cancer: A retrospective case-case study

Abstract: Abstract. Data available on lifestyle-associated hormonal and medical factors among endometrial cancer (EC)-affected women who carry the Lynch syndrome (LS) mutation is limited. The aim of the present retrospective case study was to compare the reproductive and medical history, as well as lifestyle-associated factors, among patients with LS and sporadic EC. The study population consisted of 50 verified germline mismatch repair (MMR) gene mutation carriers diagnosed with EC, and 110 sporadic EC patients. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The strengths of our study include a well-defined population of women with LS who were all verified as germline pathogenic variant carriers and were not just women who had a strong family history of EC or CRC. The study cohort identified from the LSRFi included 112 women, and the response rate was quite high (68%), which is in line with previous questionnaire-based studies among subjects with a hereditary cancer predisposition [14,15].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The strengths of our study include a well-defined population of women with LS who were all verified as germline pathogenic variant carriers and were not just women who had a strong family history of EC or CRC. The study cohort identified from the LSRFi included 112 women, and the response rate was quite high (68%), which is in line with previous questionnaire-based studies among subjects with a hereditary cancer predisposition [14,15].…”
Section: Discussionsupporting
confidence: 80%
“…The study cohort included Finnish women with inherited pathogenic MMR gene variants identified from the nationwide Finnish LS Registry (LSRFi), [11] which has been described in more detail previously [12,13,14,15]. Briefly, the LSRFi includes 300 families and approximately 1400 verified germline MMR variant carriers (http://www.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Even though inherited gene variants conferring gynecological cancer risks do not have impact on fertility as such [ 17 , 18 ], some reports have implicated that germline testing results have impact on reproductive decisions [ 8 , 9 ]. Some individuals with pathogenic MMR variants have even been reported to consider prenatal genetic testing and consider it ethical [ 8 , 19 ]. Therefore, it is very important to collect LS carriers’ subjective views and experiences of genetic testing on their reproductive decisions in order to guide and help clinicians in counselling.According to our results, testing positive for a LS-causing variant appears not to have significant impact on family planning or negative influence on relationships among Finnish women.…”
Section: Discussionmentioning
confidence: 99%
“…Staff et al reported that Type II diabetes was related to an elevated risk of LS‐EC and diabetic LS women were prone to be more overweight than nondiabetic LS women; however, they did not find any association between BMI and increased risk of LS‐EC 24 . Additionally, apart from the two studies that found no significant differences in body mass index (BMI) between MSI and microsatellite stable (MSS) patients 25,26 . Most studies 13,27‐30 suggested that patients with dMMR or MSI‐high (MSI‐H), or MMR germline PVs had a lower BMI.…”
Section: Clinicopathological Characteristicsmentioning
confidence: 99%